Aspectos produtivos e dinâmica parasitária em ovinos Santa Inês e Rabo Largo confinados com níveis de concentrado e infectados naturalmente com Eimeria spp - CARNEIRO, Weverto José Alves (2022)
The present study aimed to evaluate the productive aspects and parasitic dynamics in Santa Inês and Rabo Largo sheep confined with different levels of concentrate and naturally infected with Eimeria spp. Thirty eight male, uncastrated, five month old sheep were used, 19 animals of the Rabo Largo breed (16.68 kg ± 2.78 kg) and 19 animals of the Santa Inês breed (19.29 kg ± 3.28 kg). At the beginning of the experiment, the lambs were identified, dewormed and housed individually in pens, where they remained throughout the 51 days experimental period. The treatments consisted of two diets, one with high concentrate (CA – 70%) and the other with low concentrate (BC – 30%), with two sheep breeds (Santa Inês and Rabo Largo), totaling four treatments. The experiment was carried out in a randomized block design in a 2x2x2 factorial scheme involving the two breeds, two diets and weight gain above and below. The average daily food consumption was evaluated by the difference between the daily supply of dry matter and the respective leftovers per animal. The in vivo apparent digestibility of dry matter, organic matter, crude protein and neutral detergent fiber was also evaluated. The collections of fecal samples from these animals, for the evaluation of the Eimeria species present in these samples, were collected on days 0, 21 and 42 and later analyzed by means of coproparasitological exams. During the entire experimental period, oocysts of eight species of Eimeria were detected in the fecal samples collected, with E. ahsata being the most prevalent in both sheep breeds. GMD1 (estimated average weight gain performed at 21 days) and ADG2 (estimated average weight gain performed at 42 days) were affected by breed and diet (P<0.05). Dry Matter Intake, TDN, Dry Matter Digestibility, Crude Protein Digestibility and Ethereal Extract Digestibility showed significant interaction with Race and Diet (P<0.05). The parasitic dynamics of Eimeria species was not influenced by the breed and/or the diet provided to the animals, and among the species identified in this study, only the species E. bakuenses and E. intricata negatively affected the 1st estimate of the weight gain of the sheep. GMD 1). However, none of the species had a significant correlation (P>0.05) with the 2nd estimate of weight gain (GMD 2). Furthermore, none of the other factors evaluated (CMSg, NDT, EE and DIG) showed any type of significant correlation with the species of Emeria spp. and the amount of oocysts shed in the animals' feces decreased dramatically in the last collection (day 42) in relation to the first two (day 0 and day 21).